Recovery of physical function and patient’s satisfaction after Total Hip Replacement (THR) surgery supported by a tailored guidebook - Fortina, M.; Carta, S.; Gambera, et al., D. (Acta Biomedica Atenei Parmensis, 2005)
Background and aim of the work: The purpose of this prospective study was to give a customizedguide, describing the hospitalization period and the postoperative exercise program, to patients scheduled fortotal hip arthroplasty (THA) and to show its effectiveness on functional recovery and on patient’s satisfactionwith the rehabilitation care and with the in-hospital discharge planning after surgery.Methods: This trialincluded 365 consecutive subjects with osteoarthritis who underwent THA at the Orthopaedic and TraumatologyClinic of Siena (Italy). The Harris Hip Score (HHS), a disease specific measure, was determinedbefore and after surgery. Postoperative evaluations, associated with a Satisfaction Questionnaire, were carriedout at the time of discharge and after 3 months. Results: The overall satisfaction level was very high, both atdischarge (81±28) and at follow-up (90±17). The HHS results showed a significant (p≤0.05) improvementover time in patients with higher scores 3 months after surgery in comparison with baseline. Conclusions: Patientsreported high levels of satisfaction at the 3 month postoperative follow-up and good levels at discharge.After surgery, the highest improvements were shown in bodly pain and physical function scores.Thecurrent study showed that a customized guide was well accepted by patients withTHA and satisfie their needof information. It was also effective in improving patient’s satisfaction and early recovery of physical functionafter surgery.